Relevance of anxiety in clinical practice of Guillain-Barré syndrome: a cohort study - Raphaël Porcher; Djillali Annane; Andrea Polito; Tarek Sharshar; Takoua Merhbene; Morgane Blanc; Marion Antona; Marie-Christine Durand; Diane Friedman; David Orlikowski; Marie-Hélène Marcadet (BMJ Open)
Objectives Illness is often associated with anxiety, but few data exist about the prognostic significance of this phenomenon. To address this issue, we assessed whether patient anxiety is associated with subsequent need for intubation in Guillain-Barré syndrome (GBS).Design Incident case-cohort study.Setting Acute secondary care in a teaching hospital (France) from 2006 to 2010.Participants 110 adult GBS patients. Either language barrier or cognitive decline that precluded understanding was considered as exclusion criteria.Primary outcome Acute respiratory failure.Interventions At admission, anxiety and clinical factors (including known predictors of respiratory failure: delay between GBS onset and admission, inability to lift head, vital capacity (VC)) were assessed and related to subsequent need for mechanical ventilation (MV). Anxiety was assessed using a Visual Analogical Scale (VAS), the State Anxiety Inventory form Y1 (STAI-Y1) score and a novel-specific questionnaire, evaluating fears potentially triggered by GBS. Patients were asked to choose which they found most stressful from weakness, pain, breathlessness and uncertainty.Results 23 (22%) were subsequently ventilated. Mean STAI-Y1 was 47.2 (range 22–77) and anxiety VAS 5.2 (range 0–10). STAI was above 60/80 in 22 (21%) patients and anxiety VAS above 7/10 in 28 (27%) patients. Fear of remaining paralysed, uncertainty as to how the disease would progress and fear of intubation were the most stressful. Factors significantly associated with anxiety were weakness and bulbar dysfunction. STAI-Y1 was higher and uncertainty more frequent in subsequently ventilated patients, who had shorter onset-admission delay and greater weakness but not a lower VC. Uncertainty was independently associated with subsequent MV.Conclusions Early management of patients with GBS should evaluate anxiety and assess its causes both to adjust psychological support and to anticipate subsequent deterioration.